Board Monitoring and Antitakeover Amendments - McWilliams, Victoria B.; Sen, Nilanjan (Journal of Financial and Quantitative Analysis, 1997)
This study examines the joint influence of board composition, leadership structure, and board ownership structure on the market's reaction to corporate antitakeover amendment proposals. The stock price reaction to antitakeover amendments is more negative when the board is dominated by inside and affiliated outside board members. Further, for firms in which the CEO also chairs the board, the reaction becomes increasingly negative as inside and affiliated outside board members increase their ownership stake in the firm and proportional representation on the board. In contrast, board composition and ownership structure have little power to explain the stock price reaction when the CEO does not chair the board. We conclude that monitoring by outside independent board members is important particularly when the CEO is also the board chair. The separation of ownership and control in the corporate form of business creates potential conflicts of interest between managers and shareholders. These conflicts can be mitigated by such internal governance characteristics as the compo? sition, ownership structure, and leadership structure ofthe firm's board of directors. In this study, we analyze the joint effect of these board monitoring characteristics on the stock market response to antitakeover amendment proposals. The study of antitakeover amendments is of particular importance because of the unresolved nature of the theoretical debate surrounding the amendments and the conflicting empirical evidence. Various types of antitakeover amendments exist, but all ostensibly make the takeover of a target firm more difficult with? out the cooperation of incumbent management. The amendments can be either beneficial or detrimental, depending on how managers use them. Managers can use the amendments to extract a higher takeover bid or to entrench themselves at shareholders' expense. The empirical evidence on the market's reaction to amend? ment announcements is also mixed. For example, Linn and McConnell (1983) and